Taking into account the functional conditions in optimization of modes of the power systems by genetic algorithms - Pulatov B.M.*, Gayibov T.Sh., Abdurashidov D.Sh (International Journal of Advanced Science and Technology, 2020)
Nowadays, development of the capabilities of computational tools has created up new possibilities forthe effective use of a number of classical mathematical methods and algorithms for solving manyimportant problems in the power engineering. In particular, a set of algorithms are developed tooptimize the modes of electric power systems based on genetic algorithms. At the same time, the issuesof taking into account functional constraints in solving such problems by genetic algorithms need to beimproved. In accordance with it in this article the problems of taking into account of differentconstraints in optimization of modes of power systems using genetic algorithms are considered. Thealgorithm of optimization by genetic algorithm taking into account of functional constraints in forms ofequality and inequality by penalty functions is proposed. The results of research of proposed algorithm’sefficiency in example of optimization of mode of power system with 8 buses, 4 thermal power plants and3 transmission lines with controlled power flow are presented.